SANKSI PIDANA KEMATIAN BAGI ORANG KORUPSI DI INDONESIA (Death Criminal Sanctions For Personnel Of Corruption In Indonesia) - Irvino Rangkuti, Alvi Syahrin, Suhaidi, Mahmud Mulyadi (Fakultas Hukum Universitas Komputer Indonesia, 2021)
The application of capital punishment itself has been regulated in Indonesia as contained in the law. Article 2 paragraph (2) of Corruption Act concerning Eradication of Corruption Crimes. According to Romli Atmasasmita, it was argued that the death penalty for corruptors was effectively implemented in the People's Republic of China (PRC), and it was quite successful to reduce corruption. This certainly can be used as an example in Indonesia in imposing capital punishment for corruptors. The imposition of capital punishment for perpetrators of corruption is urgently needed as